L’exercice des biopolitiques - Antoine Doré (Revue d'anthropologie des connaissances)
This article aims to describe and think the exercise of biopolitics in focusing on the analysis of the correlative construction of an ontological referent (the population) and its equipment (infrastructure of storage and circulation of scriptural and/or biological materials) in the government management of an animal population. The article analyzes the arithmetic construction of the wolves’ population of France as a series of successive events that we propose to describe both the heterogeneity (cognitive, technical, etc.) and how they are articulated. This case study is finally an opportunity to highlight a too much anthropocentric use of the notion of biopolitics and to confront this notion to the test of a broader living-non-human conception.